Role of Solvents in Improvement of Dissolution Rate of Drugs: Crystal Habit and Crystal Agglomeration - Maryam Maghsoodi (Tabriz University of Medical Sciences, 2015)
Crystallization is often used for manufacturing drug substances. Advances of crystallization have achieved control over drug identity and purity, but control over the physical form remains poor. This review discusses the influence of solvents used in crystallization process on crystal habit and agglomeration of crystals with potential implication for dissolution. According to literature it has been known that habit modification of crystals by use of proper solvents may enhance the dissolution properties by changing the size, number and the nature of crystal faces exposed to the dissolution medium. Also, the faster dissolution rate of drug from the agglomerates of crystals compared with the single crystals may be related to porous structure of the agglomerates and consequently their better wettability. It is concluded from this review that in-depth understanding of role of the solvents in crystallization process can be applied to engineering of crystal habit or crystal agglomeration, and predictably dissolution improvement in poorly soluble drugs.